Differences in Arabic-Indonesian Vocabulary Absorption in Religious Terms: Phonological Studies - Eliana Pangestika; Tulus Musthofa; Nasiruddin Nasiruddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The purpose of this study was to find out the differences in the forms of the process of absorption of vocabulary in religious terms from Arabic into Indonesian and to find out the differences in the spelling of the absorption of the same vocabulary from Arabic into Indonesian. This study used method with a library study approach. Library Studies is an approach in research that involves an analysis of existing sources of information. This approach aims to gather knowledge through analysis of literature similar to current research. The results of this study indicate that some of the vocabulary in Indonesian is the absorption of foreign languages, one of which comes from Arabic. The arrival of the Arabs to Indonesia around the 7th century AD had the aim of trading, besides that they also spread Islam, which until now has become the majority religion in Indonesia. language absorption processes have many classifications, but in this study the researchers focused on four classifications of word absorption processes, namely Lenition, with an example of the absorption of the Arabic word “Aqidatun” to “Akidah”. Multiple Consonants, foe the example the word “Tasawwuf” to “Tasawuf”. Alpheresis, An example of the Arabic word